2021
DOI: 10.1177/0973005221998244
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Maize-based Products to the Livelihood of Smallholder Processors in Rural Northern Nigeria

Abstract: In the smallholder value chains of maize, diversification of utilisation is an essential strategy towards enhancing the benefits drivable from the increase in maize production. This article identifies the contribution of maize-based products on poverty level among smallholder processors. The study, which was conducted in 30 rural communities in northern Nigeria, involved Focus Group Discussions and survey of 300 smallholder processors of maize-based products. Descriptive and inferential analyses were used. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The findings in this study corroborate the study of Ahmadu and Edeoghon (2018) in a survey on the effect of maize production on poverty alleviation of farmers in Edo State, Nigeria and concluded that maize production has influenced significantly on the income and hence alleviating farmers poverty. Also, Ojide et al (2021) noted that diversification and necessary interventions have the capacity to remove farmers from the poverty trap in the community, hence should be encouraged.…”
Section: Cerealsmentioning
confidence: 99%
“…The findings in this study corroborate the study of Ahmadu and Edeoghon (2018) in a survey on the effect of maize production on poverty alleviation of farmers in Edo State, Nigeria and concluded that maize production has influenced significantly on the income and hence alleviating farmers poverty. Also, Ojide et al (2021) noted that diversification and necessary interventions have the capacity to remove farmers from the poverty trap in the community, hence should be encouraged.…”
Section: Cerealsmentioning
confidence: 99%